1977
DOI: 10.1159/000458785
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Esterases in Human Whole Saliva

Abstract: Whole saliva of 59 healthy persons was used for determination of esterase activity. The pattern of esterase was studied by means of isoelectrofocusing on thin-layer acrylamide gels. The esterases found in whole saliva are suggested to be derived from the cells of the tissue in the oral cavity. This origin is indicated (e.g.) by comparison between isoelectrophoretic esterase patterns of whole saliva, submandibular saliva, gingival biopsy and fibroblast culture. Antisera against partially purified saliva esteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Prchminary investigations have shown that the hydrolase activity in saliva bacteria is of minor importance for the overall activity and it is thus proposed that the mean esterase activity in sahva derives from epithehal cells. This is in accordance with observations by others (19).…”
Section: Discussionsupporting
confidence: 94%
“…Prchminary investigations have shown that the hydrolase activity in saliva bacteria is of minor importance for the overall activity and it is thus proposed that the mean esterase activity in sahva derives from epithehal cells. This is in accordance with observations by others (19).…”
Section: Discussionsupporting
confidence: 94%
“…Human Salivary Derived Esterases (HSDE) are part of the salivary group of enzymes which show strong degradative activity toward the methacrylate-based organic matrix of dental composite resin. [1][2][3][4][5] HSDE catalyze the breakdown of one of the most common monomers used in dental composites and adhesives, 2,2-[4(2-hydroxy 3-methacryloxypropoxy)-phenyl] propane (Bis-GMA), to form the degradation product 2,2-bis [4 (2,3-hydroxy-propoxy)phenyl] propane (Bis-HPPP). 5,6 Bis-HPPP by-product was previously shown to be a true marker of resin matrix biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…One class of salivary components that has some interest in terms of composite biodegradation is the esterases (Lindqvist et al, 1977).…”
Section: Introductionmentioning
confidence: 99%